STRATEGI GURU DALAM PENGEMBANGAN KARAKTER DISIPLIN PADA ANAK USIA 5-6 TAHUN - Susanti, Eli; Halida, Halida; Lukmanulhakim, Lukmanulhakim (Universitas Tanjungpura, 2024)
The purpose of this study is to characterize and gather data regarding the methods used by teachers at Al-Kautsar Islamic Kindergarten in South Pontianak to help children, ages five to six, develop disciplinary character. The contribution of this research is to increase understanding and knowledge regarding the role that teaching styles play in early childhood disciplinary character development. Descriptive qualitative research methodology is employed. Researchers who participated in this study gathered data regarding the methods used by teachers to help young children acquire disciplinary character. Two instructors from classes B3 and B4 at Al-Kautsar Islamic Kindergarten were the study's participants. In this study, documentation, interviews, and observation were the methods employed for gathering data. Data collecting, data reduction, data display, and conclusion drawing comprised the data analysis that was done. The findings of research conducted through observation, interviews, and recording demonstrate that teachers at Al-Kautsar Islamic Kindergarten in South Pontianak employ communication tactics, modeling, habituation, and storytelling to help children build disciplinary personalities. The plan of action has been carried out successfully.